2-oxoglutarate-dependent dioxygenases and BAHD acyltransferases drive the structural diversification of orobanchol in Fabaceae plants - Homma, Masato; Uchida, Kiyono; Wakabayashi, Takatoshi; Mizutani, Masaharu; Takikawa, Hirosato; Sugimoto, Yukihiro (Frontiers in Plant Science, 2024)
Strigolactones (SLs), a class of plant apocarotenoids, serve dual roles as rhizosphere-signaling molecules and plant hormones. Orobanchol, a major naturally occurring SL, along with its various derivatives, has been detected in the root exudates of plants of the Fabaceae family. Medicaol, fabacyl acetate, and orobanchyl acetate were identified in the root exudates of barrel medic (Medicago truncatula), pea (Pisum sativum), and cowpea (Vigna unguiculata), respectively.Although the biosynthetic pathway leading to orobanchol production has been elucidated, the biosynthetic pathways of the orobanchol derivatives have not yet been fully elucidated. Here, we report the identification of 2-oxoglutarate-dependent dioxygenases (DOXs) and BAHD 2 acyltransferases responsible for converting orobanchol to these derivatives in Fabaceae plants. First, the metabolic pathways downstream of orobanchol were analyzed using substrate feeding experiments. Prohexadione, an inhibitor of DOX inhibits the conversion of orobanchol to medicaol in barrel medic. The DOX inhibitor also reduced the formation of fabacyl acetate and fabacol, a precursor of fabacyl acetate, in pea. Subsequently, we utilized a dataset based on comparative transcriptome analysis to select a candidate gene encoding DOX for medicaol synthase in barrel medic. Recombinant proteins of the gene converted orobanchol to medicaol. The candidate genes encoding DOX and BAHD acyltransferase for fabacol synthase and fabacol acetyltransferase, respectively, were selected by co-expression analysis in pea. The recombinant proteins of the candidate genes converted orobanchol to fabacol and acetylated fabacol. Furthermore, fabacol acetyltransferase and its homolog in cowpea acetylated orobanchol. The kinetics and substrate specificity analyses revealed high affinity and strict recognition of the substrates of the identified enzymes. These findings shed light on the molecular mechanisms underlying the structural diversity of SLs.